A Multidisciplinary, Family-Oriented Approach to Caring for Parents After Miscarriage: The Integrated Behavioral Health Model of Care - Hiefner, Angela R.; Villareal, Astrud (Frontiers in Public Health, 2021)
Miscarriage is increasingly gaining recognition, both in scientific literature and media outlets, as a loss that has significant and lasting effects on parents, though often disenfranchised and overlooked by both personal support networks and healthcare providers. For both men and women, miscarriage can usher in intense grief, despair, and difficulty coping, and for women in particular, there is evidence of increased prevalence of depression, anxiety, and post-traumatic stress. Additionally, miscarriage can contribute to decreased relationship satisfaction and increased risk of separation, all while stigma and disenfranchisement create a sense of isolation. Despite this increased need for support, research indicates that many parents experience their healthcare providers as dismissive of the significance of the loss and as primarily focusing only on the physical elements of care. Research exploring the barriers to providers engaging in more biopsychosocial-oriented care has identified time constraints, lack of resources, lack of training in addressing loss, and compassion fatigue as key areas for intervention. This paper will review the biopsychosocial elements of miscarriage and discuss a multidisciplinary, family-oriented approach that can be implemented in healthcare settings to ensure a high quality and holistic level of care for individuals, couples, and families experiencing pregnancy loss.